FACTORS THAT INFLUENCE ADHERENCE TO BREAST TUMOR PATIENTS AT SURGICAL CLINIC IN THE BHAYANGKARA BRIMOB HOSPITAL - Wilandatika, Riski; Indawati, Ely (HEARTY, 2025)
Background: Breast tumors as one of the causes of death rates in Indonesia increase every year. For this reason, several breast tumor detection methods are currently needed to be developed to track the presence of cancer early on. Breast examinations can be carried out routinely and independently, namely by self-examination of the breasts (BSE). This method is an examination technique to find out whether there are lumps in a woman's breasts. Research Objective: To determine the factors that influence awareness compliance in breast tumor patients at the Bhayangkara Brimob Hospital Surgical Clinic. Research Method: The research approach used in this research is cross-sectional. The population in this study was 501 breast tumor patients in 2023. In the Slovin formula, the sample required is 83 respondents. The sampling technique for respondents used a simple random sampling technique. The instrument in this research was to use a questionnaire. Researchers used the Chi Square test with a confidence level of 95% or a significance level of 5%. Research Results: The results of statistical tests on the relationship between knowledge and conscious compliance showed a P value = 0.029. The relationship between motivation and conscious compliance obtained a P value = 0.000. The relationship between support from health workers and awareness of compliance was found to have a P value = 0.007. Conclusions and Suggestions: There is a relationship between knowledge, motivation and support of health workers with conscious compliance in breast tumor patients at the Bhayangkara Brimob Hospital Surgical Clinic. Suggestions for hospitals to create educational classes for patients, especially women of childbearing age, to be aware of early detection of breast tumors